2013
DOI: 10.1016/j.bbrc.2013.06.110
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic characterization of ebselen, chelerythrine and apomorphine as glutaminase inhibitors

Abstract: Glutaminase catalyzes the hydrolysis of glutamine to glutamate and plays a central role in the proliferation of neoplastic cells via glutaminolysis, as well as in the generation of excitotoxic glutamate in central nervous system disorders such as HIV-associated dementia (HAD) and multiple sclerosis. Both glutaminase siRNA and glutaminase inhibition have been shown to be effective in in vitro models of cancer and HAD, suggesting a potential role for small molecule glutaminase inhibitors. However, there are no p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 38 publications
(49 reference statements)
2
53
0
Order By: Relevance
“…To explore the role of glutaminase activity in T cell activation, naïve CD4 + T cells were stimulated with anti-CD3/CD28 in medium with or without metabolic inhibitors for 24 hrs. The glutaminase activity of these CD4 + T cells was determined using a radiolabeled assay as described (Thomas et al, 2013). We observed that activated T cells exhibited increased glutaminase activity compared to naïve T cells (Figure 2A), indicating metabolic reprogramming toward glutaminolysis.…”
Section: Resultsmentioning
confidence: 99%
“…To explore the role of glutaminase activity in T cell activation, naïve CD4 + T cells were stimulated with anti-CD3/CD28 in medium with or without metabolic inhibitors for 24 hrs. The glutaminase activity of these CD4 + T cells was determined using a radiolabeled assay as described (Thomas et al, 2013). We observed that activated T cells exhibited increased glutaminase activity compared to naïve T cells (Figure 2A), indicating metabolic reprogramming toward glutaminolysis.…”
Section: Resultsmentioning
confidence: 99%
“…(27)(28)(29), ebselen forms a selenylsulfide (-Se-S-) linkage with cysteine residues. To confirm the importance of the selenium atom in ebselen, we analyzed analogs with selenium replaced by sulfur (S-ebselen), oxygen (O-ebselen), carbon (C-ebselen) (40), or a selenoxide group (ebselen oxide) or with the phenyl ring converted to pyridine (2pyr-ebselen and 3pyr-ebselen) (41) ( Table 1). The inhibitory activity of these analogs on CTD dimerization was evaluated by TR-FRET assay.…”
Section: Hts-tr-fret For the Identification Of Inhibitors Of Ctd Dimementioning
confidence: 99%
“…The first step of glutamine metabolism is the conversion of glutamine to glutamate and ammonia, which is catalyzed by glutaminase (GLS). Bis-2-(5-phenylacetamido-1,2,4-thiadiazol-2-yl)ethyl sulfide (BPTES), which is an allosteric, time-dependent (9), and specific inhibitor of GLS1, exhibits unique binding at the oligomerization interface of the glutaminase tetramer (10,11). Although BPTES is more selective than other prototype glutaminase inhibitors, such as 6-diazo-5-oxo-L-norleucine (12) or ebselen (9), and can effectively inhibit GLS1 (13) and tumor growth (13)(14)(15), poor solubility (0.144 μg/mL) (16) has limited its clinical development.…”
mentioning
confidence: 99%